Diagnostic Yield of Decubitus CT Myelography for Detection of CSF-Venous Fistulas - Gibby, Jacob T.; Amrhein, Timothy J.; Young, Derek S.; Houk, Jessica L.; Kranz, Peter G. (American Journal of Neuroradiology, 2024)
BACKGROUND AND PURPOSE: Various imaging techniques have been described to detect CSF-venous fistulas in the setting of spontaneous intracranial hypotension, including decubitus CT myelography. The expected diagnostic yield of decubitus CT myelography for CSF-venous fistula detection is not fully established. The purpose of this study was to assess the yield of decubitus CT myelography among consecutive patients presenting for evaluation of possible spontaneous intracranial hypotension and to examine the impact of brain MR imaging findings of spontaneous intracranial hypotension on the diagnostic yield.MATERIALS AND METHODS: The study included a single-center, retrospective cohort of consecutive patients presenting during a 1-year period who underwent CT myelography and had no CSF identified in the epidural space. Patients with epidural CSF leaks were included in a secondary cohort. Subjects were grouped according to positioning for the myelogram, either decubitus or prone, and the presence of imaging findings of spontaneous intracranial hypotension on preprocedural brain MR imaging. Diagnostic yields for each subgroup were calculated, and the yield of decubitus CT myelography was compared with that of prone CT myelography.RESULTS: The study cohort comprised 302 subjects, including 247 patients with no epidural fluid. The diagnostic yield of decubitus CT myelography for CSF-venous fistula detection among subjects with positive brain MR imaging findings and no epidural fluid was 73%. No CSF-venous fistulas were identified among subjects with negative findings on brain imaging. Among subjects with an epidural leak, brain MR imaging was negative for signs of spontaneous intracranial hypotension in 22%. Prone CT myelography identified a CSF-venous fistula less commonly than decubitus CT myelography (43% versus 73%, P = .19), though the difference was not statistically significant in this small subgroup.CONCLUSIONS: We found the diagnostic yield of decubitus CT myelography to be similar to the yield previously reported for digital subtraction myelography among patients with positive findings on brain imaging. No CSF-venous fistulas were identified in patients with negative findings on brain imaging; epidural CSF leaks accounted for all cases of patients who had spontaneous intracranial hypotension with negative brain imaging findings. This study provides useful data for counseling patients and helps establish a general benchmark for the decubitus CT myelography yield for CSF-venous fistula detection.CTMCT myelographyCVFCSF-venous fistuladCTMdecubitus CT myelographyDSMdigital subtraction myelographyEBPepidural blood patchSIHspontaneous intracranial hypotension